Health of the War Worker (London : Labour Research Department)
1942-04 1942 1940s 44 pages and appetizing breakfast was supplied gratis in the canteen to every T.N.T. worker. The girls were advised to take nothing more than a cup of tea before leaving home; they then breakfasted at the Factory and their lunch was served 4½ to 5 hours later." The value of these various measures is to be judged from the results. If they are not already adopted in the filling factories in this war, the first to demand is the absolutely clean workshop and full information to every one about the dangers of T.N.T. and necessary preventive measures. Apart from clean shops, much can be done to protect the workers directly by protective clothing — caps, overalls, and boots. Caps and overalls must be laundered weekly. For T.N.T. ordinary face powder is to some degree a protection against irritation of the skin. Cream and oils are definitely dangerous to use against T.N.T. A skin varnish is sometimes recommended on the hands. C.E. or Tetryl. This is another yellow powder used in filling factories as an intermediate detonating agent. The workers using it become very stained and the yellow colour is made deeper by sunlight. This staining, of itself is not dangerous, however unsightly it may be to look like a canary. However, a form of dermatitis is common from handling this powder, especially in people with greasy skins. It starts as a red rash around the nose and under the chin, which spreads all over the face and is extremely irritating. The eyes often become very puffy and the rash may spread all over the body. However, cases recover rapidly when they no longer come into contact with the powder. Some degree of abdominal pain and discomfort is occasionally also met with in Tetryl workers. To prevent Tetryl dermatitis, the same measures are necessary as to prevent T.N.T. dermatitis. Workers should remember, when washing after working with this substance, to wash their hands before touching their faces. A protective hand cream can be used, and again powder for the face. To wash off C.E. use a soap with 5 per cent of sodium sulphite added. This ought to be supplied at the filling factory and probably is; however, a ration should be issued for home use also. 6. FACTORY MEDICAL SERVICE There is to-day no national industrial medical service, though the industrial army needs one just as much as the Armed Forces each need their trained medical personnel. This serious deficiency has been recognized by the Minister of Labour, who in July, 1940 issued the Factories (Medical & Welfare Services) Order, which 31 21/2049